Juan Rodríguez del Padrón au Concile de Bâle - Florence Serrano (Atalaya)
This article aims to exhume biographical data concerning an episode from the life of Juan Rodríguez del Padrón, in other words evidences of his stay in Basel and its function to the Cardinal Cervantes. After a brief state of the question, we present the documentation for this point of the life of an author who remains mysterious. In fact, until now, only rubrics –some contemporary scribes did precede his works– allow us to assume his presence at the Council of Basel. In light of this new information, we propose an interpretation regarding some functions assumed there and his intellectual formation.